Zakat Management: Challenges and Solution for Zakat Management Institutions in Indonesia - Rinda Asytuti; Ayu Azra Nadhifa; Nazla Aqila Zamrie; Ratih Kurnifiana (Studia Economica : Jurnal Ekonomi Islam, 2025)
The main objective of this study is to analyze the crucial role of Islamic economic institutions namely the National Zakat Agency (BAZNAS), Zakat Institutions (LAZ), and Zakat Collection Units (UPZ) in optimizing zakat management in Indonesia. In addition, this study comprehensively identifies the main challenges faced by these institutions and formulates prospective improvement strategies. Using a descriptive qualitative approach based on an in-depth literature review and relevant secondary data analysis, the results of the study confirm that Indonesia has established a solid legal and institutional framework for zakat. However, optimization is hampered by several persistent issues, including the need to improve the institutional capacity of amil, low public awareness and participation, limitations in reporting transparency, and the use of a digital system that is not yet fully integrated. Strategic steps are needed to improve the professionalism of zakat administrators, strengthen accountability through good governance, promote a more equitable and even distribution of zakat, and extensively develop technology- and digital-based zakat services. By integrating technological innovation and the principles of good governance, zakat management can be optimized. These efforts are important for realizing social justice and sustainable community welfare in Indonesia.